Spatio-temporal dimensions of draught cattle and buffaloes in Tamil Nadu - SENTHILKUMAR, G; SELVAKUMAR, K N; PRABU, M; PANDIAN, A SERMA SARAVANA; VALLI, C; JAYAVARATHAN, B (The Indian Journal of Animal Sciences, 2015)
Use of animal power generally enables farmers in Tamil Nadu as well India to increase agricultural production. The present study was conducted to explore the spatio-temporal dimensions in draught cattle and buffalo population in Tamil Nadu. Conventional analysis like mean and percentages were used for the present study. Apart from these analyses, the annual compound growth rates (ACGR) of livestock population were calculated. The scenario on cattle and buffalo population over different census periods, their compositional change, status of breed-wise cattle and population, temporal analysis on work animal population and their share to total cattle and buffalo population, scenario of draught animal population density, availability of draught animal power, district-wise variations in draught cattle and buffalo population for the state of Tamil Nadu were worked out and discussed. As a whole, the draught cattle and buffalo population in Tamil Nadu was found decreasing over years, and strategies for improvement of draught animal power in Tamil Nadu was proposed.